2008
DOI: 10.3351/ppp.0002.0001.0005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-social behaviour and disability in the UK

Abstract: Over the last ten years, the UK government has made tackling antisocial behaviour (ASB) a priority in its discourses and through the introduction of a wide range of legislative and policy measures. In the development of the new politics of conduct a number of competing discourses have emerged in which binary oppositions are employed to symbolically differentiate the law abiding from the irresponsible. The focus of this paper is on the way in which disabled people, particularly those with mental health conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A high proportion of those young people receiving ASBOs either had problems with mental health or accepted learning difficulty. Further substantive research by Nixon et al (2007) reinforces the BIBIC research's initial findings that 'young people with mental health disorders and learning difficulties may be disproportionately subject to ASBOs but little robust empirical evidence is available about the context and use of ASBOs in these circumstances' (Nixon et al, 2007: 3).…”
Section: Mental Health and Accepted Lear Ning Difficultymentioning
confidence: 90%
“…A high proportion of those young people receiving ASBOs either had problems with mental health or accepted learning difficulty. Further substantive research by Nixon et al (2007) reinforces the BIBIC research's initial findings that 'young people with mental health disorders and learning difficulties may be disproportionately subject to ASBOs but little robust empirical evidence is available about the context and use of ASBOs in these circumstances' (Nixon et al, 2007: 3).…”
Section: Mental Health and Accepted Lear Ning Difficultymentioning
confidence: 90%
“…In 2008 a Crown Prosecution Service report (Lee and Charles) indicated that a case file should contain a full assessment of the cognitive abilities of the victim prepared by a professional and relevant to the ability of the victim to take part in the criminal justice process indicating both the need to be in possession of strong evidence and a reluctance to accept the word of a disabled person. Nixon et al (2007) found that disabled people are vulnerable to being constructed as both victims and perpetrators of anti social behaviour. The mental health charity Mind (2007) maintains that the British Crime Survey should record crimes against people with mental health problems in order to establish that victimisation is unacceptable.…”
Section: Criminal Criminal Criminal Criminal Justicementioning
confidence: 99%
“…When transferred to the realm of social policy intervention, the idea of strong, cohesive communities has given rise to a series of instruments and quasi-legal sanctions which, putatively and purposefully, aim to tackle anti-social behaviour and reduce crime (Nixon et. 2008).…”
Section: The the The The Politics Of Politics Of Politics Of Politicsmentioning
confidence: 99%